Pengaruh Penggunaan Lahan Terhadap Debit Banjir Rancangan Di DAS Baubau - Nuzul, Muhammad; Achmad, Mahmud (Universitas Andalas, 2022)
ABSTRACTThis research was conducted in the city of Baubau, Southeast Sulawesi Province, the location is focused on the area directly adjacent to the Baubau River which has a river length of 15,704 Km in the Baubau catchment with an area of 76,117 Km2. which empties into residential areas as areas where seasonal floods often occur. To reduce the risk of loss due to the impact of flooding flood control efforts are needed that can be carried out properly if the flood discharge design of the repeat design can be known. This study aims to analyze changes in land use against runoff coefficient with flood discharge design period of time in Baubau watershed. The analysis used is the descriptive analysis regarding the spatial distribution pattern of land use and its effect on the runoff coefficient in 2019. Then to get the discharge plan for the return time analysis was carried out using the Nakayasu Empirical method or the Synthetic Unit Hydrograph (HSS) with rainfall data for 2010 to 2019 obtained from the BMKG Betoambari station in Baubau City. From the results of the analysis, it will be obtained the flood discharge plans for the return period of 5, 10, 20, 25, 50, and 100 years.Keywords: Baubau watershed, flood discharge, hydrograph ABSTRAKPenelitian ini dilakukan di Kota Baubau Provinsi Sulawesi Tenggara, lokasi difokuskan pada wilayah yang berbatasan langsung dengan Sungai Baubau yang memiliki panjang sungai 15.704 Km di DAS Baubau dengan luas wilayah 76.117 Km2. yang bermuara di pemukiman penduduk sebagai daerah yang sering terjadi banjir musiman. Untuk mengurangi resiko kerugian akibat dampak banjir diperlukan upaya pengendalian banjir yang dapat dilakukan dengan baik jika debit banjir desain desain ulang dapat diketahui. Penelitian ini bertujuan untuk menganalisis perubahan penggunaan lahan terhadap koefisien limpasan dengan debit banjir periode rencana waktu di DAS Baubau. Analisis yang digunakan adalah analisis deskriptif mengenai pola sebaran spasial penggunaan lahan dan pengaruhnya terhadap koefisien limpasan Tahun 2019. Kemudian untuk mendapatkan debit rencana waktu ulang dilakukan analisis dengan menggunakan metode Empiris Nakayasu atau Hidrograf Satuan Sintetis (Synthetic Unit Hydrograph). HSS) dengan data curah hujan tahun 2010 sampai dengan tahun 2019 diperoleh dari stasiun BMKG Betoambari Kota Baubau. Dari hasil analisa tersebut akan diperoleh debit banjir rencana kala ulang 5, 10, 20, 25, 50 dan 100 tahun.Kata kunci: DAS Baubau, debit banjir, hidrograf